Construction of Religious-Futuristic Character Education for Orphan Children at Ar Fachruddin and Ubay Bin Kaab Islamic Boarding School - Haironi, Adi; Sutrisno, Sutrisno; Sukiman, Sukiman (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The aim of this research is to discover the ideal construction of religious-futuristic character education for orphaned children at AR Fachruddin Orphanage Islamic Boarding School in Yogyakarta and Ubay Bin Kaab Orphanage Islamic Boarding School in Central Java. The absence of a specifically tailored character education design for orphaned children considering their specific characteristics, which is still generalized in reality, becomes the background of this research. The method used in this research is descriptive qualitative research. Data collection techniques involve observation, interviews, and documentation. Data analysis goes through stages of data condensation, data display, conclusion drawing, and data verification.Â The results of this research indicate that Religious-Conservative character education for orphaned children at Ubay Bin Kaab Islamic Boarding School is implemented through a collaboration of Islamic values with academic values supported by missionary, tarbiyah (education and guidance), worship, and social activity programs. The ideal construction of character education for orphaned children based on findings at Abdurrozaq Fachruddin and Ubay Bin Kaab Islamic Boarding Schools is Religious-Futuristic character education constructed based on the analysis of the needs of orphaned children, which is grounded in aspects of Islamic and academic values. This includes spiritual, independence, responsibility, emotional, social, creativity, and inclusivity aspects. The concept of Religious-Futuristic character education for orphaned children is expected to have implications for the availability of character education concepts specifically tailored for orphaned children.